PERSEPSI KONSUMEN TERHADAP BRAND CHEVROLET CAMARO PADA FILM TRANSFORMERS 1, 2 ,3 , DAN 4 (Studi Deskriptif Kualitatif Mengenai Persepsi Konsumen Terhadap Brand Chevrolet Camaro Yang Di Tempatkan Pad - Aulia Rahman Jati (ILKOM 16 UMY 001, 2016)
*1 Some manufacturers market their goods through the movie. They chose the movie as a media to advertise, because the placement of product placement in films is quite effective in marketing a certain brand. There are many types of products that are in the movie. One of theme brand is Chevrolet. Brand Chevrolet put its brand in the movie Transformers 1, 2, 3 and 4. The brand is making its products as the leading role in the film. The researcher saw there interest in the film. The interest of researchers brought researchers to seek to know about the perception of the brand when Brand Chevrolet Camaro that were placed in the Transformers movie turns into a robot. The method used in this research is qualitative descriptive and research sites located in Yogyakarta. espondents were interviewed ten respondents and has a Chevrolet Brand. Techniques of data collection by interview. The conversation was is done by the two parties, namely the interviewer (interviewer) who asked questions and interviewed (interviewee), which provides an answer to that question. Then the technique using the member checking the validity of the data. Based on interviews with 10 respondents, this research shows that the Camaro is a sports car that is powerful, sophisticated, and elegant. Researchers could conclude this matter based on the results of interviews with respondents. By doing placement, Chevrolet Camaro feels luxurious, powerful and elegant. This is all because depicted in the movie transformers 1, 2, 3 and 4 that the Chevrolet Camaro is a car that is powerful, sophisticated, and elegant. Robotic impression of the Chevrolet Camaro still feels because basically this sports car is designed with advanced. Respondents argued that returning to the portion that is the Chevrolet Camaro sports car in general. Chevrolet Camaro car that distinguishes the brand's competitors is packed in a film that has the robotic the movie genre.